2010
DOI: 10.1186/1471-2105-11-s9-s7
|View full text |Cite
|
Sign up to set email alerts
|

Mining multi-item drug adverse effect associations in spontaneous reporting systems

Abstract: BackgroundMulti-item adverse drug event (ADE) associations are associations relating multiple drugs to possibly multiple adverse events. The current standard in pharmacovigilance is bivariate association analysis, where each single drug-adverse effect combination is studied separately. The importance and difficulty in the detection of multi-item ADE associations was noted in several prominent pharmacovigilance studies. In this paper we examine the application of a well established data mining method known as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 25 publications
0
135
0
Order By: Relevance
“…The safety and efficacy profile of a drug can be altered significantly by the co-administration of other drugs. Multiple drug combinations in therapy are common 11 and increase the risk of adverse events since concomitant drugs can share pharmacological or metabolic pathways. In extreme cases, some drugs have caused death due to the heightened adverse effect of the drug affected by the interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy profile of a drug can be altered significantly by the co-administration of other drugs. Multiple drug combinations in therapy are common 11 and increase the risk of adverse events since concomitant drugs can share pharmacological or metabolic pathways. In extreme cases, some drugs have caused death due to the heightened adverse effect of the drug affected by the interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains a number of standard class association rule mining solutions in biomedical domain to discover patterns in medical data [90][91][92][93][94]. For instance, Yang et al [95] adopt Apriori and support and confidence as the main underlying measures to mine meaningful patterns.…”
Section: Discussion and Implications Of Findingsmentioning
confidence: 99%
“…We discuss the study performed in [11] and the observations of [30] on using association rules for mining ADE databases.…”
Section: Association Rules and Adverse Drug Reactionsmentioning
confidence: 99%
“…The simplest association rule describing an ADE has the form Vioxx → heart attack and involves one drug and one reactions. Clearly, rule of this form cannot capture ADE that result from undesirable drug interactions and this is the focus of [11]. This study is based on a set of 162,744 reports of suspected ADEs reported to AERS and published in the year 2008.…”
Section: Association Rules and Adverse Drug Reactionsmentioning
confidence: 99%
See 1 more Smart Citation